Is premeiotic genome elimination an exclusive mechanism for hemiclonal reproduction in hybrid males of the genus Pelophylax? - Doležálková, Marie; Sember, Alexandr; Marec, František; Ráb, Petr; Plötner, Jörg; Choleva, Lukáš (BMC genetics, 2016)
BACKGROUND: The ability to eliminate a parental genome from a eukaryotic germ cell is a phenomenon observed mostly in hybrid organisms displaying an alternative propagation to sexual reproduction. For most taxa, the underlying cellular pathways and timing of the elimination process is only poorly understood. In the water frog hybrid Pelophylax esculentus (parental taxa are P. ridibundus and P. lessonae) the only described mechanism assumes that one parental genome is excluded from the germline during metamorphosis and prior to meiosis, while only second genome enters meiosis after endoreduplication. Our study of hybrids from a P. ridibundus-P. esculentus-male populations known for its production of more types of gametes shows that hybridogenetic mechanism of genome elimination is not uniform. RESULTS: Using comparative genomic hybridization (CGH) on mitotic and meiotic cell stages, we identified at least two pathways of meiotic mechanisms. One type of Pelophylax esculentus males provides supporting evidence of a premeiotic elimination of one parental genome. In several other males we record the presence of both parental genomes in the late phases of meiotic prophase I (diplotene) and metaphase I. CONCLUSION: Some P. esculentus males have no genome elimination from the germ line prior to meiosis. Considering previous cytological and experimental evidence for a formation of both ridibundus and lessonae sperm within a single P. esculentus individual, we propose a hypothesis that genome elimination from the germline can either be postponed to the meiotic stages or absent altogether in these hybrids.
Keywords: Ranidae; Reproduction; rozmnožování; Hybridization, Genetic; Hemiclone; genom; mitóza; Comparative Genomic Hybridization; Genome; Meiosis; srovnávací genomová hybridizace; zvířata; hybridizace genetická; Asexual propagation; Hybridogenesis; meióza; Male; Meiotic cycle; Genomic in situ hybridization; Mitosis; karyotypizace; Rana esculenta; Animals; mužské pohlaví; Karyotyping